Unpacking the Ethics of One Health - Baard, Patrik (Journal of applied animal ethics research, 2025)
One Health (OH) is lauded for addressing how human, animal, and ecosystem health can and should be understood conjunctly. This paper will address two challenges of OH: First, conceptual unclarity and, second, the necessity of normative reasoning when planning and implementing OH projects. OH will be analytically unpacked by discussing its different conditions and the strength of and relations between those conditions. The analysis benefits reasoning about normative disagreements between the conditions before launching OH projects, and potential goal conflicts in their implementation. Both on conceptual and practical levels, the need will be stressed for ethical analysis that include human health, animal ethics, and environmental ethics, yet is also attentive to potential disagreements between these parts. After the conditions of OH are unpacked, it will be argued that balancing the conditions must be done in a transparent and systematic manner.